Penetapan Perkawinan dengan Wali Hakim Akibat Wali Adhal di Pengadilan Agama Nganjuk - Kridho Utomo, Muhammad Qoyyum; Nafik, Moh; Rachmatulloh, Mochammad Agus (Al-Syakhsiyyah: Journal of Law and Family Studies, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife, with the aim of forming a happy and eternal family based on the One Godhead. The pillars of marriage include prospective husbands, prospective wives, marriage guardians, two witnesses, and consent. The wali adhal case that took place at the Nganjuk Religious Court occurred when the prospective bride's lineage guardian hesitated or even refused to marry her daughter on the grounds that the prospective groom was not yet established in his work or because of problems with Javanese customs calculations, including house directions and calculations wetton. A guardian who does not want to marry off his daughter is called a wali 'adhal. The focus of the problem taken is how the procedure and form of the determination of guardian adhal and the basis for consideration of the panel of judges in granting the determination of the guardian judge to replace wali adhal at the Nganjuk Religious Court. It is a normative legal research, with a case approach and a conceptual approach. Using primary legal materials, secondary legal materials, and non-legal materials. The procedure and form of stipulation of guardian adhal at the Nganjuk Religious Court is in accordance with the applicable laws and regulations. The basis for the consideration of the panel of judges at the Nganjuk Religious Court which granted the determination of the guardian judge to replace the guardian adhal due to customary reasons and economic problems in the determination of 3 (three) cases was not in accordance with syar'i law. The reason does not concern the pillars and conditions for the validity of a marriage as required by syar'i law and the prevailing laws and regulations in Indonesia, so that reason must be set aside and the application granted.